'New Efforts with Old Means': Cross-cultural Symbiosis in the Works of Grieg and Grainger. Issue 1 (2nd January 2016) - Weber, Ryan
Abstract : This study examines the reciprocal relationships between language, society, and harmonic syntax. The purpose is twofold: to establish an appropriate methodology and theoretical framework with which to analyze the harmonic elements of Grieg's late vocal works and Grainger's folk-song settings; and to illustrate how folk song played a vital role in crafting a brand of universal cosmopolitanism, because both figures carried out reflexive experiments in cultural hybridity. The focus is on the final stage of Grieg's life (ca. 1900 to his death in 1907), during which divergent currents of modernism streamed across Europe. Also, while their documented friendship and mutual recourse to a cosmopolitan identity is well known, many studies still lack a terminology and deeper methodology for investigated how their cross-cultural traits were made manifest in their music. Taking the work of Graham Freeman, Walter Frisch, and Michael P. Steinberg as points of departure, this article complements their studies with an examination of significant—yet often understudied—repertoire. Providing an immanent historical approach to their works (beginning with their harmonic vocabulary and expanding outward), this article will help to define a model of modernism not predicated upon a linear progression, but by a circular teleology that questions the continuity of tradition. It is a notion of progress at the center of which is an identity molded from the multiplicity of styles, not the unicity of national idioms.